Dynamic modeling and motion control of a novel conceptual multimodal underwater vehicle for autonomous sampling. (15th November 2021) - Zhou, Hexiong; Cao, Junjun; Fu, Jian; Liu, Chunhu; Wei, Zhaoyu; Yu, Caoyang; Zeng, Zheng; Yao, Baoheng; Lian, Lian
Abstract: This paper presents a conceptual design of a novel multimodal underwater vehicle that integrates the merits of the Argo profiling float, the buoyancy-driven underwater glider and the propeller/rudder-driven underwater vehicle, which serves as a long-endurance and highly maneuverable platform for multiple-water-column ocean sampling with high spatiotemporal resolution. Key design principles of this multimodal underwater vehicle are firstly formulated to enable mode switching. The mathematical model of this proposed vehicle is derived based on unit quaternions for the three modes of locomotion, namely, Argo mode, zigzag gliding mode and propeller/rudder-driven mode (PR mode). Heading deviation arises during transition between Argo mode and zigzag gliding mode is fully revealed. To tackle this key challenge, a multi-level motion controller is developed for this hybrid vehicle, which not only guarantees rapid mode switching, but also allows the vehicle to be capable of traveling between adjacent columns in zigzag gliding mode, vertical sampling in Argo mode as well as heading correction and position compensation in PR mode. The feasibility of the mode transition, the property of the heading deviation and the performance of the devised control scheme are validated and analyzed via a series of numerical simulations and experiments. Highlights: Being up to long-endurance ocean sampling with high spatiotemporal resolution. Combine the zigzag underwater gliding, vertical profiling and general navigating. Deduce a mathematical model to completely describe the three operating modes. Propose a multi-level motion controller for multiple-water-columns sampling. Present key design principles for smooth mode switching.